Digital literacy and student creativity in learning technology: An ex post facto analysis - Nurlia; Marjuno, Siti Aisyah; Fahru, Almira Rayyah Shadria; Samaduri, Alwia (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Digital literacy is essential in higher education because students are expected not only to use technology but also to optimize it to develop creativity. This study aimed to describe students’ digital literacy and creativity levels and examine the relationship between the two variables. A quantitative ex post facto study with a correlational design was conducted involving 54 Biology Education students at Universitas Muhammadiyah Luwuk, Central Sulawesi, selected through total sampling. Data were collected using validated and reliable Likert-scale questionnaires consisting of 20 items each. Descriptive statistics and Spearman’s rank correlation were employed for data analysis. The results showed that students’ digital literacy was in the high category (M = 3.46), with the highest scores in digital security and ethics. Students’ creativity was also high (M = 3.60), with the highest scores in social impact and idea value. Correlation analysis revealed a positive relationship between digital literacy and creativity (r = 0.155, p > 0.05), indicating that the relationship was very weak and not statistically significant. These findings suggest that despite the positive trend, digital literacy cannot be definitively confirmed as having a strong contribution to student creativity. This suggests that creativity is likely influenced by various factors other than digital literacy. The findings are limited by the small sample size, single study location, and reliance on self-reported data.